2000
DOI: 10.1046/j.1439-0523.2000.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular marker‐facilitated pyramiding of different genes for powdery mildew resistance in wheat

Abstract: Breeding durable resistance to pathogens and pests is a major task for modern plant breeders and pyramiding different resistance genes into a genotype is one way of achieving this. Three powdery mildew resistance gene combinations, Pm2+Pm4a, Pm2+Pm21, Pm4a+Pm21 were successfully integrated into an elite wheat cultivar ‘Yang047′. Double homozygotes were selected from a small F2 population with the help of molecular markers. As the parents were near‐isogenic lines (NILs) of ‘Yang158′, the progenies showed good u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(78 citation statements)
references
References 17 publications
0
76
0
2
Order By: Relevance
“…This resistance gene had been widely used and had been highly effective in different parts of Europe and China years ago (Liu et al, 2000). Though the growing number of virulent strains has been reported in some parts of China, the gene occurs in high frequency in so many commercial cultivars as it is easily transferred from resistant to susceptible cultivars (Parks et al, 2008;Gao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This resistance gene had been widely used and had been highly effective in different parts of Europe and China years ago (Liu et al, 2000). Though the growing number of virulent strains has been reported in some parts of China, the gene occurs in high frequency in so many commercial cultivars as it is easily transferred from resistant to susceptible cultivars (Parks et al, 2008;Gao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Anderson (2007) reported that molecular mapping and MAS are modern tools that help in the exploitation and combining of different resistance genes into a single cultivar within a short period of time. Molecular markers are useful for discovery of new plant genotypes in segregating wheat populations (Liu et al 2000). Roelfs (1988) reported that resistance based on the generation of lines with a combination of more resistance genes is a recommended approach to offer long durable resistance.…”
Section: Marker-assisted Breedingmentioning
confidence: 99%
“…Because of this, recent plant breeding programs targeted at the identification and pyramiding of several major genes against a number of pathogenic races [11,15]. into crops including powdery mildew resistance genes (Pm2+Pm4a, Pm2+Pm21, Pm4a+Pm21) into wheat line [21], bacterial blight resistance genes (xa5, xa13, and Xa21) into rice [22], rust resistance genes (Lr41, Lr42 and Lr43) into wheat [23], late blight resistance genes (Rpi-mcd1 and Rpi-ber) into potato [24] etc. Therefore, it is important to deduce that molecular markers have remarkable applications in resistance gene/QTLs identification, mapping and pyramiding into crop plants to develop durable/ broad spectrum resistance to biotic stresses.…”
Section: Introductionmentioning
confidence: 99%